Effects of Versican V0/V1 gene silencing on biological behaviors of mouse dental papilla cells - WU Jiayan, HUANG Haiyan, SONG Chenyu, JIANG Beizhan (Editorial Office of Stomatology, 2024)
Objective To investigate the effect of Versican V0/V1 on biological behaviors of mouse dental papilla cells (mDPCs). Methods mDPCs were isolated from C57BL/6J mice at embryonic day 16.5 (E16.5). A small interfering RNA (siRNA) constructed specifically for Versican V0/V1 was transfected into mDPCs.The silencing efficiency was verified by quantitative real-time fluorescence polymerase chain reaction (qRT-PCR) and immunofluorescence staining. The proliferation rate of mDPCs was determined using EdU assay; the migration ability of mDPCs was evaluated by scratch test and transwell assay. Alkaline phosphatase (ALP) staining and alizarin red staining were used to assess the mineralization capability of mDPCs. The molecules related to odontogenic differentiation and mineralization at mRNA levels were measured by qRT-PCR. Results After siRNA transfection,the mDPCs of si-Versican V0/V1 group showed weaker proliferation and migration abilities compared with si-NC group (P<0.01). An enhanced ALP staining intensity,mineralized nodule formation and up-regulations of the molecules related to odontogenic differentiation and mineralization at mRNA levels (P<0.05) were observed in the mDPCs of si-Versican V0/V1 group. Conclusion Versican V0/V1 silencing inhibits the proliferation and migration of mDPCs,but enhances the abilities of odontogenic differentiation and mineralization.